Anaerobic co-digestion of dairy manure and maize stover with different total solids content: From the characteristics of digestion to economic evaluation. Issue 3 (June 2022) - Yan, Jing; Zhao, Yehua; He, Huiban; Cai, Yafan; Zhao, Yubin; Wang, Hongliang; Zhu, Wanbin; Yuan, Xufeng; Cui, Zongjun
Abstract: The objective of the present study is to assess the effect of the total solids (TS) content on the digestion performance, methanogenic pathways, and economic evaluation of anaerobic co-digestion with dairy manure and maize stover. The results showed that the cumulative methane yields decreased with increasing TS content, which was consistent with the maximum methane production rate and hydrolysis rate. The pH, alkalinity, soluble chemical oxygen demand, ammonium nitrogen, and volatile fatty acid content increased with increasing TS content. Analysis of the microbial community showed that the abundance of Methanosaeta decreased and Methanosarcina increased with increasing TS content, which led to the succession of the methanogenesis pathway from the acetoclastic pathway to the mixotrophic and hydrogenotrophic pathways. Results of the economic analysis indicated that the profitability of AD system increased with increasing TS content, resulting in more solid digestate being produced under the analysis conditions. Graphical Abstract: ga1 Highlights: TS content influences methane yield and volumetric methane productivity. The succession from Methanosaeta to Methanosarcina with increasing TS content. Increasing the TS content increases the net present value of anaerobic co-digestion. The solid digestate determines the net present value of anaerobic co-digestion. 14% TS is recommended for co-digestion with dairy manure and maize straw.